Risk Management in Commercial Banks in Cyprus - Mavrou, Athina (2009)
All banking institutions in the process of providing financial services face financial risks. Failure to manage these risks can result to great problems for banks or even withdrawal of a banking licence. As a result, the need to manage risks is increasingly important across all banking institutions. Risk management is not an easy task since comprehensive processes and procedures are needed to identify, measure, control, and mitigate risks. Most measures and management procedures are driven by regulations such as the Basel Committee of banking supervisory authorities and are backed up by governments and central banks. Further procedures may be developed internally by banks as a method against unpredictable risks.